2022
DOI: 10.3390/curroncol29100552
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Volume Constraints fOr oRganS At risk In Radiotherapy (CORSAIR): An “All-in-One” Multicenter–Multidisciplinary Practical Summary

Abstract: Background: The safe use of radiotherapy (RT) requires compliance with dose/volume constraints (DVCs) for organs at risk (OaRs). However, the available recommendations are sometimes conflicting and scattered across a number of different documents. Therefore, the aim of this work is to provide, in a single document, practical indications on DVCs for OaRs in external beam RT available in the literature. Material and Methods: A multidisciplinary team collected bibliographic information on the anatomical definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 117 publications
1
10
0
Order By: Relevance
“…Further examination revealed no significant neurotoxicity. 8 Our case adds to this conclusion, indicating that SRS can treat recurrent EMPs. Moreover, this case also adds to the growing body of literature for CyberKnife’s therapeutic potential in the plasmacytoma domain broadly.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Further examination revealed no significant neurotoxicity. 8 Our case adds to this conclusion, indicating that SRS can treat recurrent EMPs. Moreover, this case also adds to the growing body of literature for CyberKnife’s therapeutic potential in the plasmacytoma domain broadly.…”
Section: Discussionsupporting
confidence: 64%
“… 7 Dosimetrically, the right cochlea was exposed to a mean dose of 2.39 Gy and maximum dose of 4.38 Gy based on the general dose-volume constraints guideline for organs at risk. 8 The volume of the right cochlea receiving more than 17.1 Gy, based on the three-fraction dose-constraints guideline, was 0 mL. 9 …”
Section: Illustrative Casementioning
confidence: 99%
“…The differences between the optimized and initial calculated doses were statistically significant (paired t ‐test, p < 0.001). In addition, Table 6 shows that the reoptimized plans met the dose‐volume criteria for the other critical OARs, 19 with no significant deviations from the original plans (paired t ‐test, p > 0.05).…”
Section: Resultsmentioning
confidence: 96%
“…With regard to the oral cavity, the V30 Gy < 73% (limiting the D mean to uninvolved oral cavity) and lips should not exceed a D mean of 30 Gy [24,25]. Interestingly, the head, neck and skin GEC-ESTRO working group has recently issued some recommendations with regard to dose constraints, and found that ORN correlates with Total Physical Dose to Mandible 2cm3 ; in fact, patients receiving total physical doses greater than 61 Gy had a 20-fold increased risk of ORN [26].…”
Section: Discussionmentioning
confidence: 99%